Hubungan Sektor Pariwisata Terhadap Pemasukan Pendapatan Asli Daerah (Pad) Kabupaten Maros Periode 2014-2023Hubungan Sektor Pariwisata Terhadap Pemasukan Pendapatan Asli Daerah (Pad) Kabupaten Maros Periode 2014-2023 - Hanafi, Al Fathana; Diah Retno Dwi Hastuti; Irwandi (Primanomics : Jurnal Ekonomi & Bisnis, 2025)
This study aims to analyze the correlation or relationship between the tourism sector and the Original Regional Income  of Maros Regency for the 2014-2023 Period. This study also aims to show the relationship between the three related variables, namely the number of visitors variable, restaurant variable and hotel occupancy variable that are influential in Maros Regency from 2014 to 2023. According to BPS, Maros Regency PAD has a large source of PAD from various economic sectors. Increasing PAD in an area can include job creation and improving community welfare. Tourism is one of the sectors that can be developed into a sector that contributes to PAD with the contribution of levy and tax revenue. The data used is secondary data from 2014 to 2023 for Maros regency obtained from the Central Statistics Agency (BPS) and the Maros Regency Youth and Sports Tourism Office. The analysis was carried out by the Spearman Rank test using SPSS 25. The results of the study show that the tourism sector has a correlation or relationship with the PAD of Maros Regency. The restaurant variable had a strong relationship with PAD, while the variable of visitors and hotel occupancy had a strong relationship with PAD. This study also shows that an increase or decrease in the tourism sector has a direct impact on the amount of PAD obtained by Maros Regency, so that the tourism sector can be said to be one of the factors that can determine the stability and economic growth of Maros Regency.